Human evolution and Christian ethics - Pope, Stephen J., 1955- (Cambridge, UK ; New York : Cambridge University Press, 2007)
"Can the origins of morality be explained entirely in evolutionary terms? If so, what are the implications for Christian moral theology and ethics? Is the latter redundant, as socio-biologists often assert? Stephen Pope argues that theologians need to engage with evolutionary theory rather than ignoring it. He shows that our growing knowledge of human evolution is compatible with Christian faith and morality, provided that the former is not interpreted reductionistically and the latter is not understood in fundamentalist ways. Christian ethics ought to incorporate evolutionary approaches to human nature to the extent that they provide helpful knowledge of the conditions of human flourishing, both collective and individual. From this perspective, a strong affirmation of human dignity and appreciation for the theological virtues of faith, hope, and charity is consistent with a revised account of natural law and the cardinal virtues."--BOOK JACKET.
Evolution and religion -- The indifference of Christian ethics to human evolution -- Varieties of reductionism -- Faith, creation, and evolution -- Chance and purpose in evolution -- Human nature and human flourishing -- Freedom and responsibility -- Human dignity and common descent -- Christian love and evolutionary altruism -- The natural roots of morality -- Natural law in an evolutionary context -- Sex, marriage, and family.
Includes bibliographical references (pages 320-345) and indexes.
Print version record.
Master record variable field(s) change: 050
Keywords: Human evolution -- Religious aspects -- Christianity; Christian ethics; RELIGION -- Christian Theology -- General; Christian ethics; Human evolution -- Religious aspects -- Christianity; Moraltheologie; Evolutionäre Ethik; Christliche Ethik; Electronic books